The effects of perceived value, satisfaction, and advertising on share of wallet and word of mouth in a retailing context - Häkkinen, Juho (2016)
Customer loyalty as a topic has been of interest to managers and researchers for several decades. There are a few antecedents for explaining customer loyalty in marketing literature, and researchers have discussed the consequences of loyalty. The reason for interest toward loyalty is the wide assumption that loyal customers have higher retention rates, they buy more, and are more willing to share by word of mouth (WOM) and electronic WOM (eWOM). This is why loyalty is linked to companies' financial performance.